1999
DOI: 10.1016/s0168-6496(99)00034-3
|View full text |Cite
|
Sign up to set email alerts
|

Vital fluorescent stains for detection of stress in Pythium ultimum and Rhizoctonia solani challenged with viscosinamide from Pseudomonas fluorescens DR54

Abstract: Viscosinamide from Pseudomonas fluorescens DR54 exerts a biocontrol effect on the plant pathogenic microfungi Pythium ultimum and Rhizoctonia solani. Evidence for physiological changes in these and four other fungi was obtained by vital fluorescent staining with Calcofluor white, Nile red, Syto 13, 3,3P-diheptyloxacarbocyanine, 5-(and-6)-carboxy FDA and 5-(and-6)-carboxy SNARF-1, acetoxymethyl, acetate. Based on studies of the fungi grown on solid agar medium and Calcofluor white staining, all isolates respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
49
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 20 publications
4
49
0
1
Order By: Relevance
“…The deformities observed were similar to those reported earlier, caused due to formation of pores by interaction of biomolecules with the fungal cell membrane resulting in shrunken and empty hyphae (Romero et al, 2007;Makovitzki et al, 2007). The formation of pores further causes an increased Ca 2+ influx which has been reported to induce excessive branching of hyphae (Thrane et al, 1999;Mortel et al, 2009). The appearance of bulbous morphology may also be attributed to the effect of APB on the cytoskeletal elements, actin and tubulin leading to collapsed cytoskeleton and un-polarized growth at the tip of hyphae (Tendulkar et al, 2007).…”
Section: Discussionsupporting
confidence: 85%
“…The deformities observed were similar to those reported earlier, caused due to formation of pores by interaction of biomolecules with the fungal cell membrane resulting in shrunken and empty hyphae (Romero et al, 2007;Makovitzki et al, 2007). The formation of pores further causes an increased Ca 2+ influx which has been reported to induce excessive branching of hyphae (Thrane et al, 1999;Mortel et al, 2009). The appearance of bulbous morphology may also be attributed to the effect of APB on the cytoskeletal elements, actin and tubulin leading to collapsed cytoskeleton and un-polarized growth at the tip of hyphae (Tendulkar et al, 2007).…”
Section: Discussionsupporting
confidence: 85%
“…Microscopic analysis further revealed that the exposure of P. infestans to Mass A led to increased hyphal branching and induced the encystment of zoospores at concentrations below the CMC. Similar phenomena were described previously by Thrane et al (42,43), who exposed the oomycete Pythium ultimum and the fungus Rhizoctonia solani to viscosinamide. Those authors further hypothesized that the increased amount of branching may be the result of an increased Ca 2ϩ influx due to ion channel formation by viscosinamide (43).…”
supporting
confidence: 83%
“…The hydrophobic fatty acid tail, together with the amphiphilic property of the peptide, structure may finally play an important role in penetration and binding of CLPs within biological membranes. This in turn may support their role as surfactants and as antibiotics, e.g., disrupting membrane functions leading to excess Ca 2ϩ influx into target cells (46). Functional roles of CLP surfactants in P. fluorescens.…”
Section: Discussionmentioning
confidence: 94%